Foreign Direct Investment and Domestic Private Investment in WAEMU Countries: Crowding-in or Crowding-out? - Mano, Hahandou (International Journal of Economics and Financial Issues, 2024)
Foreign direct investment (FDI) is a particularly attractive prospect for WAEMU countries, which are constantly integrating it into their development policies. However, studies on the relationship between FDI and private domestic investment (PDI) come to contradictory conclusions. This article focused on the effect of FDI on private domestic investment over the period 1996 to 2018. The results validated the presence of cross-country dependence. The article uses Common Correlated Effect-Mean Group (CCE-MG) as the analytical technique for this purpose. The results are consistent with the “crowding-out” hypothesis of FDI on PDI.